2021
DOI: 10.3390/pharmaceutics13101572
|View full text |Cite
|
Sign up to set email alerts
|

Porous Nanomaterials Targeting Autophagy in Bone Regeneration

Abstract: Porous nanomaterials (PNMs) are nanosized materials with specially designed porous structures that have been widely used in the bone tissue engineering field due to the fact of their excellent physical and chemical properties such as high porosity, high specific surface area, and ideal biodegradability. Currently, PNMs are mainly used in the following four aspects: (1) as an excellent cargo to deliver bone regenerative growth factors/drugs; (2) as a fluorescent material to trace cell differentiation and bone f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 139 publications
(213 reference statements)
1
11
0
Order By: Relevance
“…Importantly, the hydrophilicity and nanotopography of the nanocomposite particles are also crucial properties enhancing their bioactive functions as reported by previous studies 49,50 . Ceramic particles acted as a template for the attachment of calcium secreted from osteoblast cells during bone tissue formation, whereas the hydrophilic particles with rough surfaces acted as preferential substrates for calcium deposition.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Importantly, the hydrophilicity and nanotopography of the nanocomposite particles are also crucial properties enhancing their bioactive functions as reported by previous studies 49,50 . Ceramic particles acted as a template for the attachment of calcium secreted from osteoblast cells during bone tissue formation, whereas the hydrophilic particles with rough surfaces acted as preferential substrates for calcium deposition.…”
Section: Resultssupporting
confidence: 52%
“…Importantly, the hydrophilicity and nanotopography of the nanocomposite particles are also crucial properties enhancing their bioactive functions as reported by previous studies. 49,50 Ceramic particles acted as a template for the attachment of calcium secreted from osteoblast cells during bone tissue formation, whereas the hydrophilic particles with rough surfaces acted as preferential substrates for calcium deposition. In the current research, the results demonstrated that the nanocomposite particles, especially the SrHT250, with high hydrophilicity and favored nanotopography, had a greater calcium deposition than those having poorer hydrophilicity and roughness.…”
Section: Calcium Deposition On the Core-shell Nanocomposite Particlesmentioning
confidence: 99%
“…Compared with allogeneic bone and bone gras, HAP-based drug carriers usually bind well to the surrounding host bone and promote the formation of new bone, combine with new bone, and recover the damaged bone tissue. 146 Dexamethasone (DEX)-loaded polylactic acid-glycolic acid (PLGA) microspheres were immobilized on the surface of HAP scaffolds. This composite HAP scaffold can enhance bone regeneration in vivo.…”
Section: Effect Of the Carrier On The Organismmentioning
confidence: 99%
“…Autophagy promotes the circulation of cellular components and provides energy to starving cells while simultaneously removing damaged proteins and organelles. Such functions are essential for osteocyte differentiation and immune cell polarization and are thought to play a central role in bone regeneration [ 36 ] ( Figure 3 ).…”
Section: Promising Nanomaterials For Bone Regeneration Materialsmentioning
confidence: 99%
“… Schematic of autophagy-derived regulation in the differentiation/function of osteoclasts/osteoblasts and osteoimmunology. Reprinted from reference [ 36 ]. M1, M1 macrophage; M2, M2 macrophage; IL-6, interleukin 6; iNOS, inducible nitric oxide synthase; IL-10, interleukin 10; TGF-β, transforming growth factor-beta; RANKL, receptor activator of nuclear factor-κB ligand; BMSC, bone marrow stem cell.…”
Section: Figurementioning
confidence: 99%